2014
DOI: 10.1111/jbi.12334
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climatic niche suitability and geographical overlap on hybridization patterns among southern Californian oaks

Abstract: Aim Information on the association between geographical patterns of hybridization and the climatic niche requirements and co‐occurrence of the species involved can provide important insights that further our understanding of the factors promoting the formation of hybrid zones. Here, we test whether climatic niche suitability explains patterns of hybridization beyond spatial overlap in distributions of the geographically restricted Engelmann oak (Quercus engelmannii) and the widespread scrub oak species complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 84 publications
2
66
1
Order By: Relevance
“…; Ortego et al . ). With the exception of Q. dumosa and Q. pacifica , our analyses also indicate a lack of intraspecific genetic structure across the entire ranges of the different taxa, even when some species ( Q. berberidifolia , Q. durata ; Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Ortego et al . ). With the exception of Q. dumosa and Q. pacifica , our analyses also indicate a lack of intraspecific genetic structure across the entire ranges of the different taxa, even when some species ( Q. berberidifolia , Q. durata ; Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Ortego & Bonal ; Ortego et al . ), we excluded hybrids/introgressed individuals from the data sets ( q < 0.90; e.g. Besnard et al .…”
Section: Methodsmentioning
confidence: 99%
“…Nei's gene diversity is weakly dependent on the loss of rare alleles, whereas allelic richness is sensitive to the number of alleles whatever their prevalence (Allendorf 1986). Our study showed that climatically stable areas cannot be the exclusive, decisive factor determining the patterns of genetic structure and diversity in circumboreal taxa as was suggested by Ortego et al (2014). Therefore, when we used the chloroplast and nuclear markers, genetic diversity was shown either to potentially remain at present-day levels or decline, while rare and unique cpDNA and ITS haplotypes in C. calyculata and L. b ssp.…”
Section: Discussionmentioning
confidence: 50%
“…De La Torre predominantly outcrossing because of self-incompatibility mechanisms and severe inbreeding depression; their usually large natural distribution areas; their efficient pollen and seed flow (including long-distance gene flow); and the absence of strong reproductive barriers between closely related species. Recent studies show the prevalence of hybridization in several different taxa such as Picea (De La Torre et al 2014aHamilton et al 2015;Sun et al 2014;Hasselhorst and Buerkle, 2013), Pinus (Zhou et al 2010;Li et al 2010;Gao et al 2012;Cullingham et al 2013;, Populus (Lexer et al 2007;Thompson et al 2010;Lindtke et al 2014), Juglans (Pollegioni et al 2013), Fraxinus (Gerard et al 2013;Thomasset et al 2013), Quercus (Lepais and Gerber 2010;Zeng et al 2011;Ortego et al 2014), Eucalyptus (McKinnon et al 2010, and Aesculus (Thomas et al 2008). …”
Section: Natural Hybridization In Tree Speciesmentioning
confidence: 99%
“…Although several studies have suggested the presence of environmental-dependent hybrid zones such as the mosaic zone (Quercus: Guichoux et al 2013;Ortego et al 2014;Populus: Lidkte et al 2014;Lexer et al 2010;Pinus: Cullingham et al 2012;and Picea: Hamilton et al 2013) and the bounded hybrid superiority (De La Torre et al 2014a), to explain the maintenance of hybrid zones in tree species, very few have performed experimental tests on fitness differentials between hybrids and pure species (common-garden studies), or tests of reproductive barriers. The estimation of lifetime fitness is extremely complicated in tree species due to their long-generation times; therefore, fitness proxies (such as germination, survival, growth, and disease susceptibility) have been used to test the fitness of pure species and hybrids (De La Torre et al 2014a;Roe et al 2014;Abadie et al 2011).…”
Section: Environment Role In the Maintenance Of Hybrid Zonesmentioning
confidence: 99%